Measurement of environmental indicators in recovered springs of the Igarapé D'Alincourt (Research, Society and Development, 2022)
To measure the efficiency of Area Recovery Programs, several environmental indicators can be used. Therefore, the objective was to evaluate, through environmental indicators, the recovery in springs of the Igarapé D'Alincourt. The study was carried out in the municipality of Rolim de Moura, on line 180 on the south side, in four springs, and the selection criterion was the realization of the recovery in the springs in the year 2008 to 2011. For the evaluation, an on-site visit was carried out and the potential macroscopic parameters for field surveys were verified. There was a quantification of the macroscopic environmental indicators present in the APP's areas, and values were assigned: the closer to 5 maximum grade for the indicator group, the greater the quality of the evaluated and more preserved spring. The interaction matrix that attributes value to the indicator was used, being Good (6), Regular (3), Bad (1). The best performances for macroscopic indicators were found in springs N3, N1, N2 and N4, in descending order. The best environmental indicators of ecosystem recovery were found in N3, N1 and N2, with the lowest score being in N4. The studied springs N1 and N3 have good macroscopic and ecosystem recovery indicators, on the other hand, N2 and N4 have the lowest environmental indicators, which suggests an intervention to improve their environmental indicators of recovery.